Quality of Public Services In Service Office Population and Civil Registration - Supriyanto, Didik (International Publisher, 2023)
This study aims to find out a descriptive description of Public Services and the Quality of Public Services at the Office of the Population and Civil Registry Office of Batu City. things, such as efforts to increase the professionalism of the apparatus which are still lacking, carrying out services that are not yet timely. The findings from the research show that there are a number of things that lead to poor service in terms of the professionalism of the apparatus and the punctuality of work. All of these things need to be improved by paying attention to the qualifications of the apparatus in providing services. Both in terms of Reliability (Reliability), Responsivenees (responsiveness), and Assurance (Guarantee). Supporting factors such as work motivation and cooperation. Inhibiting factors such as Human Resources (HR), Facilities and Infrastructure.